SASARAN SILEK JUNGUIK SATI DALAM LANGKAH AMPEK NAGARI BATU TABA KABUPATEN TANAH DATAR - Yan Stevenson; Auliana Mukhti Maghfirah; Oktavianus Oktavianus; Ernawita Ernawita (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This research aims to understand the preservation of the "langkah ampek" tradition and the method of character formation among the younger generation in the Batu Taba Nagari, Tanah Datar District, and its impact on the development of silek (a traditional martial art) today. The research method used in this study is qualitative research with a descriptive analysis approach, where all the data collected in the field are compiled, described, and analyzed according to the discussed issues. The cultural theory by Jacobus Ranjabar is employed to analyze this research. In line with the research object, the results reveal that pencak silat (martial arts) has its own unique style and characteristics in both offensive and defensive techniques. The rapid development of culture and technology has had an impact on the development of silat in the archipelago, leading to a decline in the interest of the younger generation in the development of this cultural art form, resulting in a gradual erosion of the culture over time. The local richness of various silat styles in Minangkabau, which are owned by the three regions (Luhak), namely Luhak nan Tuo/Tanah Datar, Luhak Agam, and Luhak 50 Koto, is one of the cultural treasures. The phenomenon of the development of traditional silek is concerning due to the decreasing interest of the younger generation. However, in the Batu Taba Nagari, Tanah Datar District, there is a considerable enthusiasm for silek, which is well-received by the local community. The target of Junguik Sati plays a role in shaping the character of the younger generation through the Langkah Ampek pattern.